PENGARUH KETIDAKPUASAN KONSUMEN DAN KARAKTERISTIK KATEGORI PRODUK TERHADAP KEPUTUSAN PERPINDAHAN MEREK DENGAN KEBUTUHAN MENCARI VARIASI SEBAGAI VARIABEL MODERASI - Suharseno, Teguh; Hidayat, Riskin; Liana Dewi, Dian Ayu (Buletin Studi Ekonomi, 2014)
Abstract : The Influence of Consumer Dissatisfaction and Product Category and Characteristics to Switch Brand Decision with The Needs to Find Variation as Moderating Variable. This study aims to identify the influence of consumer dissatisfaction and product characteristics to brand switching mobile phones with need for variation as moderating variable. Data were processed and analyzed using the Moderated Regression Analysis (MRA). Hypothesis testing using t test and determination with a significance level of 5%. Product Moment formula and Cronbach Alpha of consumer choice use for measuring the validity and reliability. These results indicate that consumer dissatisfaction and characteristics of the product category significant and positively effect the consumers in making decisions on brand switching mobile phone products, as well as the need for variation can moderate the influence of consumer dissatisfaction and the characteristics of the product category brand switching decisions on mobile phone products.
Keywords: consumer dissatisfaction, product characteristics, the need for variation, and brand switching.